Kaum Muda Katolik Kota Malang, Aset Gereja dan Budaya di Masa Depan - Steprih, Kristophorus Retas (Perspektif, 2018)
The youth of today is living in a so-called urbanized culture. This kind of culture is present everywhere, spreading along the time, and arrives to the city of Malang as well. With its counterpart, popular culture, it gives way for both positive and negative impacts, which are very challenging for the youth.This young generation, the future of the church and of the society at large, is expected very much but not without anxiety. The writer assumes that the coming of new culture such as urban culture, globalization, and all kind of development dan progress provides the youth, on the one hand, an opportunity to find out and elaborate their individualistic identity and, on the other, a crisis in their faith. The article then tries to work out these two opposing sides of life, the spiritual aspect and the physical one.